Effect of investigation intensity and treatment differences on prostate cancer survivor's physical symptoms, psychological well-being and health-related quality of life: a two country cross-sectional study. Issue 12 (19th December 2016) - Gavin, Anna T; Donnelly, David; Donnelly, Conan; Drummond, Frances J; Morgan, Eileen; Gormley, Gerard J; Sharp, Linda
Abstract : Aim: To investigate effects on men's health and well-being of higher prostate cancer (PCa) investigation and treatment levels in similar populations. Participants: PCa survivors in Ireland where the Republic of Ireland (RoI) has a 50% higher PCa incidence than Northern Ireland (NI). Method: A cross-sectional postal questionnaire was sent to PCa survivors 2–18 years post-treatment, seeking information about current physical effects of treatment, health-related quality of life (HRQoL; EORTC QLQ-C30; EQ-5D-5L) and psychological well-being (21 question version of the Depression, Anxiety and Stress Scale, DASS-21). Outcomes in RoI and NI survivors were compared, stratifying into 'late disease' (stage III/IV and any Gleason grade (GG) at diagnosis) and 'early disease' (stage I/II and GG 2–7). Responses were weighted by age, jurisdiction and time since diagnosis. Between-country differences were investigated using multivariate logistic and linear regression. Results: 3348 men responded (RoI n=2567; NI n=781; reflecting population sizes, response rate 54%). RoI responders were younger; less often had comorbidities (45% vs 38%); were more likely to present asymptomatically (66%; 41%) or with early disease (56%; 35%); and less often currently used androgen deprivation therapy (ADT; 2%; 28%). Current prevalence of incontinence (16%) and impotence (56% early disease, 67% late disease) did not differ between RoI and NI. In early disease, only current bowel problems (RoI 12%; NI 21%) differed significantly in multivariate analysis. In late disease, NI men reported significantly higher levels of gynaecomastia (23% vs 9%) and hot flashes(41% vs 19%), but when ADT users were analysed separately, differences disappeared. For HRQoL, in multivariate analysis, only pain (early disease: RoI 11.1, NI 19.4) and financial difficulties (late disease: RoI 10.4, NI 7.9) differed significantly between countries. There were no significant between-country differences in DASS-21 or index ED-5D-5L score. Conclusions: Treatment side effects were commonly reported and increased PCa detection in RoI has left more men with these side effects. We recommended that men be offered a PSA test only after informed discussion.